2022
DOI: 10.1002/mop.33581
|View full text |Cite
|
Sign up to set email alerts
|

Passive Q‐switched operation of Tm:YAP laser with a TaTe2 saturable absorber

Abstract: In this paper, a Tm:YAP all-solid-state continuous wave (CW) and passive Q-switched (PQS) laser were experimentally proved by using a TaTe 2 -based saturable absorber (SA) for the first time. Under the CW mode, the maximum output power was 4.99 W and the slope efficiency was 29.8%. Based on TaTe 2 SA, the shortest pulse width of 585 ns at the central wavelength of 1987.9 nm was obtained with the pump power of 17.73 W, corresponding to single-pulse energy of 9.7 µJ and an average output power of 1.86 W. Also, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 48 publications
(72 reference statements)
0
10
0
Order By: Relevance
“…In addition, due to the inherent properties of molecules and their interactions with the external environment, any molecular absorption spectrum exhibits a spectral line broadening around its center wavelength that follows a certain line shape rule, as mentioned in formula (2). Considering the atmospheric pressure characteristics of the actual atmosphere, the Doppler broadening in the gas system is far less than the collision broadening, so it can be assumed that the line shape of molecular absorption spectra in the atmosphere can be characterized using a Lorentzian line shape [16][17][18][19][20] :…”
Section: Atmospheric Attenuation Of Dpal Transmissionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, due to the inherent properties of molecules and their interactions with the external environment, any molecular absorption spectrum exhibits a spectral line broadening around its center wavelength that follows a certain line shape rule, as mentioned in formula (2). Considering the atmospheric pressure characteristics of the actual atmosphere, the Doppler broadening in the gas system is far less than the collision broadening, so it can be assumed that the line shape of molecular absorption spectra in the atmosphere can be characterized using a Lorentzian line shape [16][17][18][19][20] :…”
Section: Atmospheric Attenuation Of Dpal Transmissionmentioning
confidence: 99%
“…Laser wireless energy transmission technology is more suitable for long-distance air and environments that are sensitive to electromagnetic interference, such as remote charging of unmanned aerial vehicles and energy transmission for outer spacecraft. Diode-pumped alkali laser (DPAL) is considered as the most promising lasers for application in laser long distance energy transfer due to their high atmospheric transmission efficiency, excellent beam quality, good matching of wavelengths with the response range of Si and GaAs photovoltaic cells that can achieve high photoelectric conversion efficiency, [15][16][17] and high enough output power potential. 18 DPAL laser energy transfer efficiency is affected by various components, including the electro-optical conversion rate of the laser, antenna emission/receiving efficiency, laser transmission efficiency in the atmosphere, and the photoelectric conversion rate of photovoltaic cells.…”
Section: Introductionmentioning
confidence: 99%
“…Niu et al demonstrated a PQS Tm:YAP laser by using TaTe 2 -based SA. 62 However, there is a lack of comprehensive research on the laser modulation performance of VTe 2 , and no experimental investigations have been conducted on its potential applications in saturable absorption. Moreover, the weak van der Waals interactions between the layers make it easier to exfoliate few-monolayer thicknesses from the bulk material.…”
Section: Introductionmentioning
confidence: 99%
“…Experimentally, Zhang et al and Shang et al investigated the nonlinear optical properties in a mode-locked fiber laser with NbTe 2 –PVA film SA as the mode-locked device and proved that NbTe 2 demonstrates as a broadband SA to produce mode-locked pulses within fiber lasers. Niu et al demonstrated a PQS Tm:YAP laser by using TaTe 2 -based SA . However, there is a lack of comprehensive research on the laser modulation performance of VTe 2 , and no experimental investigations have been conducted on its potential applications in saturable absorption.…”
Section: Introductionmentioning
confidence: 99%
“…With the benefits of eye safety and significant water molecule absorption, pulsed lasers in the 2-μm wavelength region have been employed extensively in various fields, including material processing, environmental monitoring, gas detection, medical, radar, pump source of optical parametric oscillators for mid-infrared (mid-IR) sources, and others. [1][2][3][4][5][6][7] Using a diode-pumped thulium-doped gain medium is one of the ways to achieve 2 μm waveband laser output on the 3 F 4 -3 H 6 transition from the solid-state laser (SSL). Tm:YAP crystals with strong anisotropic characteristics, larger stimulated emission cross-section, and broad emission spectrum are suitable as gain media for SSLs.…”
Section: Introductionmentioning
confidence: 99%